(untitled) - Keogh, Jim (New York, N.Y., 2005)
This book offers: An easy way to understand JavaScript; A quiz at the end of each chapter; A final exam at the end of the book; No unnecessary technical jargon; A time-saving approach.
Keywords: JavaScript ( Computer program language )